Effect of vascular endothelial growth factor gene transfer on infarct size, left ventricular function and myocardial perfusion in sheep after 2months of coronary artery occlusion - Vera Janavel, Gustavo L. (2012)
Background: In large mammalian models of acute myocardial infarction (AMI), plasmid-mediated vascular endothelial growth factor (pVEGF) gene transfer has been shown to induce angio-arteriogenesis, proliferation of myocyte precursors and adult cardiomyocyte mitosis, reducing infarct size at 15days after coronary artery occlusion. However, it is unknown whether these effects persist at longer follow-up times, nor how they affect cardiac performance. We thus assessed infarct size, left ventricular (LV) function and perfusion in 2-month-old ovine AMI. Methods: Adult sheep with coronary artery occlusion were randomized to blindly receive ten intramyocardial injections of 3.8mg of pVEGF or empty plasmid distributed at the infarct border. Three and 60days later, LV perfusion (single-photon emission computed tomography) and function (stress echocardiography) were assessed. Finally, hemodynamics (LV catheterization), scar size and peri-infarct histology were studied. Results: Infarct size was 30% smaller in pVEGF-treated sheep (23.6±1.9% versus 32.7±2.7% of the LV; p<0.02). Percentage fractional shortening and wall thickening at the infarct border improved after pVEGF, as did myocardial perfusion and LV wall motion under pharmacological stress. Global LV function did not differ between groups, although the force-frequency response was preserved in pVEGF group and lost in placebo animals. These effects were associated with angio-arteriogenesis and proliferation of cardiomyocyte precursors. Conclusions: In sheep with AMI, pVEGF gene transfer affords long-term infarct size reduction, yielding regional LV function and perfusion improvement and reducing remodeling progression. These results suggest the potential usefulness of this approach in the clinical setting.